Impacts of Industry 4.0 in sustainable food manufacturing and supply chain. (18th June 2020) - Ojo, Olumide Olajide; Shah, Satya; Coutroubis, Alec
Integration of sustainability and sustainable practices have been of paramount importance within most manufacturers' supply chain environment globally. Apart from the fact that every organisation now use this to improve on their corporate social responsibility (CSR), this is also used as an opportunity to manage production and services within most firms efficiently. This sustainability is now a strategy adopted by most businesses to meet their customers' expectation considering the sustainable society awareness of which food manufacturing is not an exception. The use of several innovative strategies and incorporation of Industry 4.0 has been employed by some food manufacturers to meet up with this sustainability. This paper, through a qualitative research study, seeks to bridge the interconnection between Industry 4.0 and sustainable practices within food manufacturing supply chain.